1970
DOI: 10.1111/j.1432-1033.1970.tb01037.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Mixed Function Oxidase with its Substrates and Associated Redox Transitions of Cytochrome P‐450 and Pyridine Nucleotides in Perfused Rat Liver

Abstract: 1. The interactions of a 'Type I' compound, hexobarbital, and of a 'Type 11' compound, metyrapone, with the mixed function oxidase were demonstrated by spectrophotometric techniques in hemoglobin-free perfused livers from phenobarbital-treated rats. The binding signal for hexobarbital occurred when cytochrome P-450 was mainly oxidized (normoxic perfusion) or reduced (anoxic perfusion), The binding signal disappeared as hexobarbital was metabolized.2. Functional aspects were demonstrated by simultaneous reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1970
1970
1983
1983

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Similar methods might be applied for analysis of contributions of other systems. For example, specific transitions in extramitochondrial [27,28] Fig. 11) and acetate (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similar methods might be applied for analysis of contributions of other systems. For example, specific transitions in extramitochondrial [27,28] Fig. 11) and acetate (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Dual wavelength absorbance photometry by sinusoidal wavelength modulation [7] was used for more sensitive study of absorbance changes as a function of time (see also [8]). Bandwidth of monochromatic light was 4 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Since the P-450 -CO complex increased upon the addition of hexobarbital in livers from fed, phenobarbital-treated rats, Sies a n d Brauser concluded that NADPH supply was not ratelimiting in livers from fed, phenobarbital-treated rats [27]. It would be interesting, therefore, t o identify factors responsible for the metabolism of drugs other than 7-ethoxycoumarin in periportal and pericentral regions of the liver in various nutritional states.…”
Section: Discussionmentioning
confidence: 99%